2016
DOI: 10.1063/1.4961469
|View full text |Cite
|
Sign up to set email alerts
|

Membrane-type resonator as an effective miniaturized tuned vibration mass damper

Abstract: Damping of low frequency vibration by lightweight and compact devices has been a serious challenge in various areas of engineering science. Here we report the experimental realization of a type of miniature low frequency vibration dampers based on decorated membrane resonators. At frequency around 150 Hz, two dampers, each with outer dimensions of 28 mm in diameter and 5 mm in height, and a total mass of 1.78 g which is less than 0.6% of the host structure (a nearly free-standing aluminum beam), can reduce its… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
25
0

Year Published

2017
2017
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(25 citation statements)
references
References 20 publications
0
25
0
Order By: Relevance
“…The steel plate was hanging by soft threads through the two clear holes near its top edge at about 10 cm apart. For frequency response measurements, the plate at the position 7 cm from the lower right corner along the plate diagonal line was attached to a shaker similar to the one reported earlier 43 . The response displacement was measured by a miniature accelerometer at the corresponding position relative to the left upper corner.…”
Section: Basics Of Coherent Super Decaymentioning
confidence: 99%
See 3 more Smart Citations
“…The steel plate was hanging by soft threads through the two clear holes near its top edge at about 10 cm apart. For frequency response measurements, the plate at the position 7 cm from the lower right corner along the plate diagonal line was attached to a shaker similar to the one reported earlier 43 . The response displacement was measured by a miniature accelerometer at the corresponding position relative to the left upper corner.…”
Section: Basics Of Coherent Super Decaymentioning
confidence: 99%
“…The miniature TMD’s used in this study were made of decorated membrane resonators (DMR’s) reported earlier 43,45 . The photo of one of the DMR’s used in the experiments is shown in the insert of Fig.…”
Section: Basics Of Coherent Super Decaymentioning
confidence: 99%
See 2 more Smart Citations
“…However, most studies on MAMs were primarily focused on sound isolation or absorption applications, with a limited number of studies on vibration control applications. Sun et al [21] investigated the membrane-type resonator's performance as a tuned mass damper. The research work indicated that by attaching two membrane-type resonators to an aluminium beam, the structural vibration can be attenuated effectively.…”
Section: Introductionmentioning
confidence: 99%